Knowledge Intensive Business Services: The Russian Experience - Marina Doroshenko; Ian Miles; Dmitry Vinogradov (Foresight and STI Governance)
Knowledge-Intensive Business Services (KIBS) are seen to be a core sector of the so-called ‘knowledge economy’, and already play an important role in developed economies. They a both innovate themselves and provide their clients with knowledge and learning opportunities. This paper examines the status of KIBS in Russia, and explores some key issues in their role in innovation using data from surveys of KIBS firms and their clients in Russia. We note that KIBS are often highly customized, and many new services prove difficult to replicate. KIBS are closely tailored to solving the problems of specific customers, and thus these services typically involve KIBS consumers in a co-production process. Both the formal supplier and the formal user of the service are engaged together in service production, allowing for mutual knowledge transfers and learning. Using KIBS is shown to affect customers’ propensity to innovate, confirming the importance of this sector for the innovation system.